Sequence stratigraphy of the Middle Jurassic Yan’an Formation (NE Ordos Basin, China), relationship with climate conditions and basin evolution, and coal maceral’s characteristics - Lv, Dawei; Shen, Yangyang; van Loon, A. J. Tom; Raji, Munira; Zhang, Zhihui; Song, Guangzeng; Ren, Zhouhe; Wang, Yujia; Wang, Dongdong (Frontiers in Earth Science, 2023)
The Yan'an Formation of the Ordos Basin in North China is among the largest and most extensively studied Jurassic coal reservoirs in the world. The lacustrine Yan'an Formation was investigated near Dongsheng (Ordos Basin, China) in its sequence-stratigraphic context, to understand the factors that controlled the peat accumulation and the cyclicity in the coal-bearing strata. Nine facies, grouped into two facies associations, jointly composed two third-order sequences. These represent lowstand system tracts, extended (lacustrine) system tracts and highstand system tracts. The sequence stratigraphic framework could be established on the basis of correlations of cores and logging from several wells. It appears that the coal development was controlled partly by fluctuations of the lake level. The sequence development controlled the vertical distribution of the coal seams, which mainly developed during extended lacustrine system tracts (= during transgressive stages of the lake) and the early stage of highstand system tracts. Sequence stratigraphy and maceral analysis indicate that basin subsidence and climate were the main controlling factors for the development of the coal seams and the coal-bearing succession. A generic model was established to show the lateral and vertical distribution of coal seams in the large, subsiding lacustrine coal basin with no significant folding or faulting. Special attention is paid to the changing climate conditions. The findings are considered to help deepen the theory of coal formation; they will also help increase the efficacy of coal exploitation in basins such as the Ordos Basin.